EDUCATION FOR DEMOCRATIC CITIZENSHIP: ERNEST SIMON’S IDEALS OF LIBERAL DEMOCRACY AND CITIZENSHIP EDUCATION IN ENGLAND, 1934-1944 - Ku, Hsiao-Yuh (Historia y Memoria de la Educación, 2018)
In 1934, with the increasing threats to democracy from such totalitarian nations as Italy and Germany, Sir Ernest Simon (1879-1960), a British industrialist and former Liberal MP, founded the Association for Education in Citizenship (AEC) to advocate reform in citizenship education for cultivating democratic citizenship. Simon’s efforts and his distinctive approach towards citizenship education, which was different from that of his contemporaries such as Fred Clarke, R. H. Tawney, and Richard Livingstone, have been discussed and acknowledged by historians. Even so, few historians have attempted to grasp Simon’s ideals of liberal democracy and how his democratic ideals were reflected in his views of citizenship education. Due to a lack of connection between Simon’s democratic ideals and his views of citizenship education, previous literature not only fails to explain in what way Simon’s approach towards citizenship was «liberal», but also misinterprets Simon’s ideas of citizenship education. In view of this, the current paper explores Simon’s views of democratic citizenship and his campaign for a new citizenship education in relation to his ideals of liberal democracy in order to provide a better understanding of Simon’s approach towards citizenship education. Moreover, it will help shed some light on the development of citizenship education in twentieth-century England.